Penggunaan Metode Pembelajaran Treffinger untuk Meningkatkan Kemampuann Pemecahan Masalah Geografi Siswa Kelas X SMA Negeri 1 Kecamatan Kapur IX - Tika, Wisi Yulian; Nofrion, Nofrion (TSAQOFAH, 2023)
In the world of education, problem solving abilities are very important to have, there are many learning methods that can support students' problem solving abilities, one of which is the Treffinger method. The purpose of this research is to determine the increase in students' problem solving abilities. This research uses quantitative methods with the type of experimental research. The population in the study were class X students using the Rendom Sampling technique with samples from class XE 3 and In collecting data, testing techniques were used to see the level of students' problem solving abilities. Hypothesis testing analysis of the data in this research uses a difference test (t test). The results of data processing found an increase in students' problem solving abilities by applying the Treffinger method compared to conventional models.